2006
DOI: 10.1016/j.neuropharm.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid receptor agonist WIN 55,212-2 attenuates the effects induced by quinolinic acid in the rat striatum

Abstract: The cannabinoid receptor agonist WIN 55,212-2 attenuates the effects induced by quinolinic acid in the rat striatum AbstractThe ability of CB 1 receptors to regulate the release of glutamate in the striatum, together with the finding that, in experimental models of Huntington disease (HD), both endocannabinoid levels and CB 1 receptor densities are reduced, has prompted the investigation on the neuroprotective role of the cannabinoids in HD. Quinolinic acid (QA) is an excitotoxin that, when injected in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 36 publications
7
65
0
3
Order By: Relevance
“…In experimental and human HD, corticostriatal glutamatergic transmission is severely impaired (for review see [36]), and QA lesions result in a secondary dying back of these terminals [37]. Relative upregulation of this CB 1 receptor population could conceivably represent a compensatory response, damping the excessive corticostriatal glutamatergic drive that results from QA infusion [38] and reducing the excitotoxic mechanisms underlying HD [39]. However, within the caudate-putamen, CB 1 receptors are also expressed on striatal GABAergic interneurons that are labelled with parvalbumin and a few interneurons of the cholinergic population [40], from which their contribution to the observed effect cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental and human HD, corticostriatal glutamatergic transmission is severely impaired (for review see [36]), and QA lesions result in a secondary dying back of these terminals [37]. Relative upregulation of this CB 1 receptor population could conceivably represent a compensatory response, damping the excessive corticostriatal glutamatergic drive that results from QA infusion [38] and reducing the excitotoxic mechanisms underlying HD [39]. However, within the caudate-putamen, CB 1 receptors are also expressed on striatal GABAergic interneurons that are labelled with parvalbumin and a few interneurons of the cholinergic population [40], from which their contribution to the observed effect cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by an exhaustive preclinical work with positive results in a broad spectrum of animal models of HD (e.g., R6/2 mice, quinolinate-lesioned mice, 3-nitropropionate-or malonate-lesioned rats), which confirmed the benefits of cannabinoids against most of the cytotoxic stimuli acting in this disease (reviewed in [1,2,131]). For example, compounds targeting the CB 1 R preserved striatal neurons in studies conducted in a rat model that relies on quinolinate-induced excitotoxic damage [132]. The relevance of these receptors in HD was also demonstrated in a genetic model of the disease, R6/2 mice, in which CB 1 R activation again preserved striatal neurons from death, whereas striatal damage was aggravated in R6/2 mice having a genetic deficiency in CB 1 R [133].…”
Section: Cannabinoids and Chronic Neurodegenerative Disorders: III Hdmentioning
confidence: 94%
“…This may explain why an early stimulation of these receptors may dampen their impairment, thereby maintaining their capacity to inhibit the excitotoxic events that initiate the damage to striatal neurons [132], although such an approach is unlikely to work at later symptomatic stages that are characterized by an important loss of CB 1 R-containing striatal neurons [117]. However, as recent study unequivocally demonstrated that CB 1 R-dependent neuroprotective activity in HD is predominantly derived from a restricted population of these receptors on cortical glutamatergic neurons that project to the striatum and that are preserved during the progression of HD rather than from the CB 1 R located on striatal projection γ-aminobutyric acid (GABA)-ergic neurons that are progressively lost during disease progression [142], supporting the relevance of these receptors as potential targets for a neuroprotective therapy with cannabinoids in HD.…”
Section: Cannabinoids and Chronic Neurodegenerative Disorders: III Hdmentioning
confidence: 99%
“…Importantly, following on from an extensive preclinical evaluation using different experimental models of HD (reviewed in [4] and [5]), clinical tests are now being performed with cannabinoids. Using experimental models that reproduce different cytotoxic stimuli that operate in HD pathogenesis, for example rodents treated with mitochondrial toxins (e.g., inhibitors of mitochondrial complex II), quinolinate-lesioned mice, or transgenic mice bearing mutated forms of human huntingtin, preclinical studies with cannabinoids demonstrated preservation of striatal neurons [6][7][8][9][10][11]. The beneficial effects of cannabinoids were exerted through multiple mechanisms of action, including cannabinoid receptor type 1 (CB 1 ) activation (e.g., excitotoxic models [8,11]), cannabinoid receptor type 2 (CB 2 ) activation (e.g., inflammatory models [10]), and CB 1 /CB 2 -independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%